Development of a core set of quality indicators for paediatric primary care practices in Europe, COSI-PPC-EU. - Ewald, Dominik A.; Huss, Gottfried; Auras, Silke; Caceres, Juan Ruiz-Canela; Hadjipanayis, Adamos; Geraedts, Max (European Journal of Pediatrics, 2018)
Paediatric ambulatory healthcare systems in Europe are, because of historical reasons, diverse and show strikingly different outcomes. All across Europe, the benchmarking of structures, processes and outcomes could reveal opportunities for improving Paediatric Primary Care (PPC). The aim of this study was to develop a set of Quality Indicators (QIs) to assess and monitor PPC in Europe. In a three-step process, we used the available external evidence and European expert consensus in a modified RAND/UCLA Appropriateness Method (RAM) to develop an indicator set. (1) A broad literature and online research of published QI and guidelines yielded an inventory of 1516 QI. (2) A collaborative panel of paediatric senior experts from the European Academy of Paediatrics (EAP) and the European Confederation of Primary Care Paediatricians (ECPCP) from 15 European countries participated in a first consensus process to reduce the initial indicator inventory by eliminating not PPC-focused indicators and duplicates. (3) In a second consensus process, the panel rated the QI regarding validity and feasibility. The final QI set "COSI-PPC-EU" consists of 42 indicators in five categories of PPC: (A) health promotion/prevention/screening (13 QI), (B) acute care (9 QI), (C) chronic care (8 QI), (D) practice management (3 QI) and (E) patient safety (9 QI).Conclusion: COSI-PPC-EU represents a consented set of a limited number of valid quality indicators for the application in paediatric primary care in different healthcare systems throughout Europe. What is Known: • Paediatric ambulatory healthcare systems in Europe are diverse and show strikingly different outcomes. • There are known gaps in quality performance measures of paediatric primary care in Europe. Pre-existing sets of quality indicators are predominantly limited to national populations, specific diseases and hospital care. What is New: • A set of 42 quality indicators for primary paediatric care in Europe was developed in a multi-country collaborative effort. The method combined a systematic literature review and a consensus process among European paediatric experts. • The quality indicator set can facilitate quality improvement of PPC. After studying the feasibility, providers can use COSI-PPC-EU to monitor, compare and improve performance of practices, regions and countries.